Continuous production of 7-Aminocephalosporanic acid by immobilized cells of Pseudomonas diminuta - Nigam V.K.; Kundu S.; Ghosh P. (My University, 2025)
The continuous production of 7-ACA with immobilized whole cells of P. diminuta was carried out in a tubular glass reactor at optimal conditions. The biocatalyst was prepared by gel entrapment using chitosan, geletin and agar as immobilizing agents. The micro-organism was characterized in terms of cell-to-carrier ratios, diffusional properties, as well as storage and operational stability, etc., towards the production of 7-ACA. It was found that a cell to carrier ratio of 0.45 and a flow rate of 120 mL h-1, respectively, were most suitable for the conversion of CPC to 7-ACA. Operational stability was highest with chitosan, with a half life of 2106 h followed by gelatin, then agar as immobilizing supports.